KLASİK DÖNEM İSLAM TARİHÇİLERİNİN TARİH ANLAYIŞI - Mehmet Mahfuz Söylemez (İslami İlimler Dergisi)
The word “history” which is expressed to be the Arabic version of the persian word “mah-ruz”, has been subject to an expansion in its meaning since its has emerged. Becoming an exclusive name for to describe the science of history over time, it has gained meaning which is very close to modern definition of history. The orthography of islamic history, has created a very distinctive method since the very beginning and this method has been implemented meticulously. In some respecet, this method which is believed to have some similarities with the method developed by French Anales School, has been implemented until the emergence of modern historiography. In this article, the above-mentioned topics are discussed briefly.